2020
DOI: 10.1055/a-1154-8832
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxing Activity of Stilbenoid and Phenanthrene Derivatives from Brasiliorchis porphyrostele: Involvement of Smooth Muscle CaV1.2 Channels

Abstract: Five compounds, 3,4′-dihydroxy-3′,5,5′-trimethoxydihydrostilbene, 1; 3,4′-ihydroxy-3′,5′-dimethoxydihydrostilbene, 2; 3,4′-dihydroxy-5,5′-dimethoxydihydrostilbene, 3; 9,10-dihydro-2,7-dihydroxy-4,6-dimethoxyphenanthrene, 4; and the previously unreported 1,2,6,7-tetrahydroxy-4-methoxyphenanthrene, 5 were isolated from the South American orchid, Brasiliorchis porphyrostele. An in-depth analysis of their vascular effects was performed on in vitro rat aorta rings and tail main artery myocytes. Compounds 1 – 4 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Dalbergia isolates were assessed for their effects on I KCa1.1 . Under the conditions used in the present experiments, the outward current mostly consisted of iberiotoxin-sensitive I KCa1.1 [ 48 ]. Figure 6 A shows the traces of I KCa1.1 elicited with clamp pulses to 70 mV from a V h of −40 mV, under control conditions and after the cumulative addition of 30 and 100 µM biochanin A.…”
Section: Resultsmentioning
confidence: 99%
“…Dalbergia isolates were assessed for their effects on I KCa1.1 . Under the conditions used in the present experiments, the outward current mostly consisted of iberiotoxin-sensitive I KCa1.1 [ 48 ]. Figure 6 A shows the traces of I KCa1.1 elicited with clamp pulses to 70 mV from a V h of −40 mV, under control conditions and after the cumulative addition of 30 and 100 µM biochanin A.…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial dysfunction contributes to the pathogenesis of microvascular diabetic complications. Thus, considering that (a) endothelial relaxation depends on several agents such as NO [ 44 ], prostacyclin [ 45 ], and/or endothelium-derived hyperpolarizing factor (EDHF) [ 46 ], (b) endothelial-dependent vasorelaxation is altered in diabetes [ 47 ], and (c) the NO synthesis was involved in 5-HT 1D renal sympatho-inhibitory effect in normoglycaemic rats [ 18 ], we determined the possible role of these vasodilator agents in the serotonergic inhibitory action in diabetic rats using ODQ (a guanylyl cyclase inhibitor), indomethacin (a COX 1/2 inhibitor), or glibenclamide (an ATP-sensitive K + channels blocker) [ 48 , 49 , 50 ]. As was observed in normoglycaemic animals, only the NO pathway is involved in the 5-HT 1D renal sympatholytic action in diabetes, which is also in agreement with previous results by us in the diabetic pithed rat model [ 22 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not a secret that orchids are widely used in traditional medicine for the treatment of different health conditions such as for instance hypertension, tuberculosis, paralysis, stomach disorders, or arthritis [ 83 ]. Some of them are used as emetics, aphrodisiacs, vermifuges, bronchodilators, or sex stimulators, or to treat scorpion stings and snake bites [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Representatives of Maxillaria sensu lato are not an exception and are also widely used in traditional medicine for their antispasmodic and anti-inflammatory activities [ 85 , 86 ]. Waratchareeyakul et al [ 83 ] have for example reported vasorelaxant activity of stilbenoid and phenanthrene derivatives from Brasiliorchis porphyrostele (Rchb.f). The major compounds identified in dichloromethane extract from B. schunkeana were 7,9-di-tert-butyl-1-oxaspiro(4,5)deca-6,9-diene-2,8-dione (77.06%) and 2,5-di-tert-butyl-1,4-benzoquinone (16.65%).…”
Section: Discussionmentioning
confidence: 99%